DEVELOPMENT OF AL-QURAN HADITH TEACHING MODULE FOR LEARNING AT MTS - Siti Nurkayati (Journal of Pedagogical Content Knowledge, 2025)
This study aims to develop a contextual-based teaching module for Qur'an Hadith learning at MTs Khozinatul Ulum Blora. The background of this research stems from the lack of appropriate teaching materials that meet students’ needs and local context in Qur'an Hadith instruction. This research employs a Research and Development (R&D) approach, adapting Borg and Gall's (1983) model into seven key stages: identifying potentials and problems, initial data collection, product design, design validation, design revision, limited trial, and final product revision. Instruments used include expert validation questionnaires, student response surveys, and learning outcome tests. The validation results from experts categorized the module as highly feasible. The limited trial results showed a significant increase in student learning outcomes, with the average pretest score of 63.2 rising to 90.6 in the posttest. Student responses indicated that the module is engaging, easy to understand, and supports independent learning. The developed module proves effective in enhancing student achievement and also increases their motivation and interest in contextually learning the Qur'an Hadith. This research recommends broader implementation and further development with large-scale trials.